Género, alimentos y derechos: revisión del estado de la cuestión y análisis crítico - Ramírez Huaroto, Beatriz (2019)
This article will analyze Food Law from a gender perspective. Thus, the author develops the normative and jurisprudential framework on the subject in Peru. Likewise, quantitative and qualitative data on the resolution of conflicts regarding this topic are reviewed, which will allow to glimpse the interaction between the normative, structural and political-cultural components of the legal phenomenon Finally, the author develops an analysis on the application of a perspective gender in the regulation and practice of alimony.